The use of applied improvisation at university: a mini-review - Jouin, Marine; Sharvadze, Isabella; Fekete, Judit; Longuépée, Héloïse; Thomas, Hadrien; Grados, Clarisse; De Wever, Julie; Gignon, Maxime; Hainselin, Mathieu (Frontiers in Psychology, 2026)
AimThis mini review aimed to synthesize current evidence on applied improvisation programs in higher education across disciplines, identifying their impact, implementation, evaluation methods, and future research directions.MethodsFollowing PRISMA-ScR guidelines, a systematic search was conducted across six databases, covering publications from 1999 to 2024. Inclusion criteria encompassed empirical studies involving university populations engaging in theatrical or applied improvisation interventions. After screening, 54 relevant studies were included. Data extracted included study characteristics, participant demographics, intervention methods, evaluation methodologies, and outcomes.ResultsMost studies originated from the United States (70.4%), targeting students (85.2%), particularly in healthcare education (61.1%). Interventions varied from single workshops to multi-session courses, aiming to improve skills such as communication (62.9%), empathy (25.9%), collaboration (25.9%), confidence (22.2%), and stress management (14.8%). Evaluations often relied on satisfaction surveys or in-house questionnaires, with only 27.8% using standardized tools. Methodological variability and reliance on self-reported measures limited comparability and generalizability of the results.ConclusionApplied improvisation demonstrates potential as an innovative educational tool in higher education, enhancing key skills across various disciplines. However, significant methodological limitations—including heterogeneous interventions and assessments—hinder generalization of findings. To advance the field, future research should develop standardized assessment tools, establish consistent intervention protocols, and conduct randomized controlled longitudinal studies to assess the effectiveness and the durability of outcomes. Strengthening interdisciplinary collaborations and employing rigorous research methodologies are essential to optimize the use of applied improvisation in higher education.